2018
DOI: 10.1080/23335432.2018.1454342
|View full text |Cite
|
Sign up to set email alerts
|

An applied paradigm for simple analysis of the lower limb kinematic chain in explosive movements: an example using the fencing foil attacking lunge

Abstract: A simple method to quantify the kinematic chain in a propulsive task would facilitate assessment of athlete effectiveness. The study's aim was to assess if the kinematic chain distinguishes between skill levels. Fencers were separated into two groups based on attacking lunge ability (7 skilled; 8 novices). Rear leg 3D joint angular extension velocity magnitudes and timings, sword kinematics and rear leg kinetics were obtained in the propulsion phase of the attacking lunge. Skilled fencers obtained greater swor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Previous studies used different methods to set the lunge distance. Some studies allowed the fencers to stand a self‐selected distance deemed to be their optimal distance (Gholipour et al., 2008; Guilhem et al., 2014; Hassan & Klauck, 1998; Mulloy et al., 2016; Tsolakis & Vagenas, 2010; Tsolakis, Kostaki, & Vagenas, 2010; Turner et al., 2016). A study in 2000 set the horizontal distance between the toe of the rear foot in en garde position and the target using the standing height of each participant multiplied by 1.5, and allowed the fencers to adjust the distance slightly by themselves (Williams & Walmsley, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies used different methods to set the lunge distance. Some studies allowed the fencers to stand a self‐selected distance deemed to be their optimal distance (Gholipour et al., 2008; Guilhem et al., 2014; Hassan & Klauck, 1998; Mulloy et al., 2016; Tsolakis & Vagenas, 2010; Tsolakis, Kostaki, & Vagenas, 2010; Turner et al., 2016). A study in 2000 set the horizontal distance between the toe of the rear foot in en garde position and the target using the standing height of each participant multiplied by 1.5, and allowed the fencers to adjust the distance slightly by themselves (Williams & Walmsley, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The sword velocity was used to represent the lunge speed instead of HPV in this study. However, they did not define the sword velocity clearly, and if it would be influenced by the possible movements of the wrist and arm extension (Mulloy, Mullineaux, & Irwin, 2016) is unknown. Another study (Gholipour et al., 2008) compared the moving patterns of the forward knee joint during the fencing lunge between elite fencers and novices by recording kinematic data of their lunge movements using three high‐resolution cameras, and found that both the elite fencers and novices flexed the forward knee joint before the extension when initiating the lunge.…”
Section: Introductionmentioning
confidence: 99%
“…The BFb was presented using a bar-chart, with colour coding used to display sequencing information using peak joint angular velocity timing (green-signifying proximal to distal sequencing; red identifying joints that were out of sequence; figure 2). Participants were instructed to beat their personal best joint angular velocity extensions, whilst also maintaining proximal to distal sequencing linked with successful attacking lunge performance (Mulloy et al, 2018). The personal best trial was displayed as an overlaid red dotted line for each joint, using the trial with the greatest ankle plantar-flexion maximal velocity during that session.…”
Section: Methodsmentioning
confidence: 99%
“…A propulsive skill, such as the fencing attacking lunge, serves as useful skill to assess the influence of kinematic changes on external kinetics due to; the stationary starting position; whole lower-limb proximal-to-distal sequencing underpinning CoM propulsion (Mulloy et al, 2018); and an increase in horizontal centre of mass (CoM) velocity having a direct link with improved performance (Bottoms et al, 2013). Therefore, the aims of this research were twofold; to 1) assess the effectiveness of a biofeedback intervention targeting whole lower limb kinematics during a propulsive skill, and 2) investigate relationships in the biofeedback targeted kinematics on untargeted external kinetics underpinning CoM propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…The BFb was displayed as a bar-chart with a colour coding systemused to demonstrate sequencing information using joint angular velocity timing (greensignifying proximo-distal sequencing; red identifying joints that were out of sequence;figure 2). Participants were instructed to obtain proximo-distal sequencing, which has been linked with successful fencing attacking lunge performance(Mulloy et al, 2018), while also trying to beat their personal best maximal joint angular velocities that was displayed as an overlaid red dotted line for each joint. The personal best trial was the trial with the greatest ankle plantarflexion maximal velocity during that session.…”
mentioning
confidence: 99%